2021
DOI: 10.1038/s41467-021-22830-9
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule imaging reveals replication fork coupled formation of G-quadruplex structures hinders local replication stress signaling

Abstract: Guanine-rich DNA sequences occur throughout the human genome and can transiently form G-quadruplex (G4) structures that may obstruct DNA replication, leading to genomic instability. Here, we apply multi-color single-molecule localization microscopy (SMLM) coupled with robust data-mining algorithms to quantitatively visualize replication fork (RF)-coupled formation and spatial-association of endogenous G4s. Using this data, we investigate the effects of G4s on replisome dynamics and organization. We show that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 78 publications
6
59
0
Order By: Relevance
“…These data support computational studies that have suggested more than 350,000 PG4s reside outside of telomeric regions; with the inclusion of non-canonical motifs, the total number of PG4 motifs is over 700,000 in the human genome [50,51]. Recently, single-molecule fluorescence microscopy was combined with unbiased pattern recognition algorithms to analyze G4 structures associated with replication [52]. In U2OS cells, ~2% of replisomes, identified by PCNA and MCM helicase antibodies, colocalize with G4 structures.…”
Section: Relationship Of G4 Formation To Dna Replicationsupporting
confidence: 78%
“…These data support computational studies that have suggested more than 350,000 PG4s reside outside of telomeric regions; with the inclusion of non-canonical motifs, the total number of PG4 motifs is over 700,000 in the human genome [50,51]. Recently, single-molecule fluorescence microscopy was combined with unbiased pattern recognition algorithms to analyze G4 structures associated with replication [52]. In U2OS cells, ~2% of replisomes, identified by PCNA and MCM helicase antibodies, colocalize with G4 structures.…”
Section: Relationship Of G4 Formation To Dna Replicationsupporting
confidence: 78%
“…Several reports have described the formation of G4 structures within endogenous chromatin, and their ability to recruit transcription factors to promote active transcription [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The location of those G4 structures was revealed using an antibody-based G4 chromatin immunoprecipitation sequencing (G4 ChIP–seq) approach [ 21 ], and suggests that they play a crucial role in critical cellular processes such as DNA replication [ 29 , 30 ], DNA damage repair [ 26 ], transcription [ 22 , 23 ], translation [ 31 ] and epigenetic modifications [ 32 ]. By using G4 ChIP–seq, Hänsel-Hertsch et al showed a reduction in the number of detected DNA G4s (10,000) in genome [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory function of G4 structures is contrasted by their potential to induce genome instability. Depending on the location and the time, the formation of G4s can cause genome instability by altering transcription, causing replication fork stalls or inducing mutations [17,21,[33][34][35][36][37]. To preserve genome stability helicases, ensure the correct unfolding of G4 structures within cells [38].…”
Section: Introductionmentioning
confidence: 99%